Spatial regulation of contractility by Neuralized and Bearded during furrow invagination in Drosophila. Issue 1 (December 2017) - Perez-Mockus, Gantas; Mazouni, Khalil; Roca, Vanessa; Corradi, Giulia; Conte, Vito; Schweisguth, François
Abstract Embryo-scale morphogenesis arises from patterned mechanical forces. DuringDrosophila gastrulation, actomyosin contractility drives apical constriction in ventral cells, leading to furrow formation and mesoderm invagination. It remains unclear whether and how mechanical properties of the ectoderm influence this process. Here, we show that Neuralized (Neur), an E3 ubiquitin ligase active in the mesoderm, regulates collective apical constriction and furrow formation. Conversely, the Bearded (Brd) proteins antagonize maternal Neur and lower medial–apical contractility in the ectoderm: inBrd -mutant embryos, the ventral furrow invaginates properly but rapidly unfolds as medial MyoII levels increase in the ectoderm. Increasing contractility in the ectoderm via activated Rho similarly triggers furrow unfolding whereas decreasing contractility restores furrow invagination inBrd -mutant embryos. Thus, the inhibition of Neur by Brd in the ectoderm differentiates the mechanics of the ectoderm from that of the mesoderm and patterns the activity of MyoII along the dorsal–ventral axis. In theDrosophila embryo, increased cortical contractility in ventral cells causes furrow formation and gastrulation. Here, the authors show that contractility is regulated by Neuralized (an E3 ubiquitin ligase) in ventral cells, and that inhibiting this process with Bearded in the ectoderm causes furrow invagination.